2012
DOI: 10.4103/0019-5359.110896
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of swellings of head and neck region

Abstract: FNAC is a simple, quick, inexpensive, and minimally invasive technique to diagnose different types of head and neck swellings. It could differentiate the infective process from neoplastic one and avoids unnecessary surgeries. Thus, FNAC can be recommended as a first line of investigation in the diagnosis of head and neck swellings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 9 publications
17
40
1
Order By: Relevance
“…Our study is similar to the study by Rathod GB et al which showed female preponderance and similar age group. [12] Out of the lymphadenopathies, reactive hyperplasia constituted the majority of the cases (28.57%) and granulomatous lesions (25%). Results by Lawrence et al 2003 showed 59% of cases with reactive hyperplasia followed by granulomatous lesion (41%).…”
Section: Discussionmentioning
confidence: 96%
“…Our study is similar to the study by Rathod GB et al which showed female preponderance and similar age group. [12] Out of the lymphadenopathies, reactive hyperplasia constituted the majority of the cases (28.57%) and granulomatous lesions (25%). Results by Lawrence et al 2003 showed 59% of cases with reactive hyperplasia followed by granulomatous lesion (41%).…”
Section: Discussionmentioning
confidence: 96%
“…Rathod et al made clinicopathological correlation of head and neck lesions and assessed the frequency of incidences of different sites, age groups, sex, and distribution among inflammation and neoplastic lesion. 10 Fine-needle aspiration diagnosis was correlated with details of relevant clinical findings and investigations. Out of 200 fine-needle aspiration procedures, 52% were of thyroid, 28.50% were of lymph node, 11% from salivary gland, and 4% from soft tissue and miscellaneous swellings.…”
Section: Discussionmentioning
confidence: 99%
“…In thyroid colloid/nodular goiter is predominant lesion 5 cases were reported (50%) while follicular adenoma is reported in 4 cases (40%) and single case of papillary carcinoma was detected in 60 yr old male Muddegowda et al (14) and Rathod et al (15) also found thyroid lesions as the predominant site of FNAC in their study with colloid goiter as the predominant finding. Female preponderance was observed in thyroid lesions in our study, similar findings reported by Rathod et al (15) and Muddegowda et al (14) . In lymph node lesions tubercular lymphadenitis was the most common pathological findings which is in concordance with Bhagat et al (16) , Sharma et al, Ahmad T et aland El Haq et al Single case of hodgkins lymphoma was reported in 60 yr old male.…”
Section: Resultsmentioning
confidence: 85%